Shocks and Structural Breaks : Labor Market Reforms in the United Kingdom - Prasad, Eswar (IMF Working Papers; Working Paper ;, 1994)
This paper analyzes the effects of the labor market reforms launched in the early 1980s by the Conservative government led by Mrs. Thatcher. It is argued that the increase in the growth of labor productivity in manufacturing after 1980 as well as the improvement in the responsiveness of employment to variations in output can be largely attributed to the success of the reforms in reducing industrial disputes and removing a number of structural impediments in the labor market. However, the reforms did not succeed in moderating real wage growth or improving the tradeoff between wage inflation and unemployment. This is attributed to certain aspects of the wage bargaining system and the influence of relative wage norms in the process of wage determination.